Effects of low temperature on distribution and metabolism enzyme activity of carbon and nitrogen of Medicago ruthenica (L.). (11th September 2022) - Yang, Yanting; Dong, Jiaqi; Gu, Rui; Shi, Ruru; Shi, Fengling
Abstract: Low temperature is one of the abiotic factors that limit the biomass of Medicago ruthenica (L.), and carbon and nitrogen have important roles in the plant's growth and development. However, the information on the distribution of carbon and nitrogen under low temperature conditions is limited. In this study, we investigated the influence of carbon and nitrogen distribution on M. ruthenica (L.) Trautv. cv. 'Zhilixing' based on 13 C and 15 N isotope tracers in two temperature‐controlled chambers (4–10°C and 25°C, respectively) for 30 days. Results showed that under low temperature, plant height significantly decreased by 22.74%, whereas the ratio of underground to aboveground biomass considerably increased by 146.31% compared to the control plants at 30 days. Moreover, low temperature stress significantly increased the activities of sucrose synthase and glutamine synthase in leaves, shoots and roots. The total carbon content and the abundance of 15 N increased in leaves, shoots and roots under low temperature, with a greater level of increase in shoots than in leaves and roots. The weight of leaves, shoots and roots was correlated with δ 15 N. Hence, low temperature inhibited growth and promoted the transport of carbon and nitrogen.